Diet and the context of fruit industry - Marek Kruczek; Dorota Gumul; Elżbieta Olech; Anna Areczuk; Halina Gambuś; Barbara Drygaś; Paweł Drygaś (Economic and Environmental Studies (E&ES), 2017)
Poland is a big world producer of fruits and fruit products. The fruit industry leaves in large scale during fruit processing production waste called fruit pomace. Generally, the fruit pomace is thrown away on the prisms and calling production residues. Fruit pomace after processing still holds high amount of valuable compounds beneficial for human health, like dietary fibre, pectin and minerals. It also contains the broad spectrum of polyphenols which have high antioxidant activity. Therefore, it has big potential for being reutilized into pro-health edible products, not only for animal feed or pectin production as it mostly happens today. Many of the pomace components may be also successfully used in non-food industries like fuel industry; or be bio-transformed in the other way. For that reason, the use of fruit pomace as a raw material should be extended to production of more effective products to ensure sustainable development. Due to the problem of production residues disposal, it is advisable to present the possibility of further utilization of fruit waste and the consequent.
Keywords: 330; fruit pomace; waste utilization; fruits